Growth, Surface Morphology and Mechanical Properties of Potassium Hydrogen Sulphate Single Crystals for Antimicrobial and Third-Order NLO Applications - Thilaga, K.; Selvarajan, P.; Kader, S.M. Abdul (Physics and Chemistry of Solid State, 2023)
A good quality single crystal of potassium hydrogen sulphate (KHS) has been grown and subjected to characterization techniques including single crystal X-ray diffraction, scanning electron microscope, hardness test, Z-scan and antimicrobial test. The single crystal X-ray diffraction study discloses the orthorhombic system of the KHS crystals. The SEM analysis shows the formation of tiny hillocks in the KHS crystal. Vickers microhardness test was utilized for testing the mechanical hardness of the grown KHS crystals. Moreover, the mechanical parameters such as elastic stiffness constant and yield strength were also determined. The nonlinear optical properties such as nonlinear susceptibility, nonlinear refractive index, and nonlinear absorption coefficient were estimated by Z scan analysis. In addition, antimicrobial activity was performed against certain pathogens for medication applications.